Improving Critical Thinking Through Effective Argumentation - Buribaeva, Aziza (MMIT Proceedings, 2025)
This article explores the relationship between critical thinking and the argumentative function of language. Tracing the origins of critical thinking back to Socratic questioning, the authors define it as a reasoned process of evaluating information. They emphasize the importance of argumentation as the highest form of language function, to illustrate the progression from expressive to descriptive and finally to argumentative language. The article further analyzes the conditions for successful communication, including clarity of expression, truthfulness, normative correctness, and sincerity, and delves into the concept of "proposition" within speech acts and discourse.